2002
DOI: 10.1080/10473220252864978
|View full text |Cite
|
Sign up to set email alerts
|

In-Use Testing and Interpretation of Chemical-Resistant Glove Performance

Abstract: Issuing gloves to workers is the most common approach to protecting against skin contact with hazardous chemicals. Typically, glove materials are selected and duration of wear is estimated based on comparisons of laboratory test data. Those who select the glove materials often fail to verify their selections by testing the glove during actual use. This failure poses a common but potentially serious hazard to workers. Although methods are available for assessing permeation rates during actual use, such testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…A discussion about available in-use sampling techniques and the development of toxicologically based comparison criteria is the subject of a companion article. (48) Unfortunately, detailed studies that evaluate the actual performance of glove use in workplaces and the way some of the variables mentioned affect the performance are virtually nonexistent. The available eld studies evaluated only a small number of workers and present a mixed picture of success and failure related to the use of CPC.…”
Section: Resultsmentioning
confidence: 98%
“…A discussion about available in-use sampling techniques and the development of toxicologically based comparison criteria is the subject of a companion article. (48) Unfortunately, detailed studies that evaluate the actual performance of glove use in workplaces and the way some of the variables mentioned affect the performance are virtually nonexistent. The available eld studies evaluated only a small number of workers and present a mixed picture of success and failure related to the use of CPC.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, it is important for employers to select the most appropriate glove for a particular application and to determine how long it can be worn, and whether it can be reused. However, the authors are unaware of any approaches that are presently available for the practical performance of these evaluations or for the interpretation of the results, apart from some recently published proposals Boeniger and Klingner 2002).…”
Section: Occupational Safety and Health Administrationmentioning
confidence: 98%
“…Cherrie et al 2004 argued that the Kp value may be changed further when sweat is present as the permeation rate through the protective layer is limited by the skin permeation rate at saturated water concentration (the maximum concentration that the sweat may achieve). In fact, , the compounds should first dissolve in sweat to permeate skin since sweat reduces the concentration gradient between the stratum corneum and the subcutaneous tissues (Boeniger and Klingner 2002;Chan et al 2010). However, water solubility is not the only factor according to Williams et al (2005), who suggested that sweat influences the permeation.…”
Section: Discussionmentioning
confidence: 99%